2014
DOI: 10.7567/jjap.54.01af05
|View full text |Cite
|
Sign up to set email alerts
|

Towards understanding plasma formation in liquid water via single bubble studies

Abstract: Plasma-in-water based technological approaches offer great potential to addressing a wide range of contaminants threatening the safety of freshwater reserves. Widespread application of plasma-based technologies, however require a better understanding of plasma formation processes in water and the nature of the plasma-driven chemistry in solution. In this paper, we survey the scope of the threat to freshwater via contamination from a variety of sources, the status of conventional treatment technologies, the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 56 publications
0
8
1
1
Order By: Relevance
“…This is completely different from the experimental results reported by Foster and Gucker [26,27]. They observed the discharge in a cavitation bubble produced by applying an ultrasonic power to water.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…This is completely different from the experimental results reported by Foster and Gucker [26,27]. They observed the discharge in a cavitation bubble produced by applying an ultrasonic power to water.…”
Section: Discussioncontrasting
confidence: 86%
“…The experimental results suggest that the cavitation bubble is conductive and it has free charges. This may be a unique feature of the cavitation bubble induced by liquid-phase laser ablation, since the deformation of the cavitation bubble is not observed when it is produced by an ultrasonic power [26,27]. Since it has been found that the growth field of nanoparticles in liquid-phase laser ablation is the inside of the cavitation bubble [36][37][38][39][40], the present experimental results may explain the origin of the high zeta potential of the colloidal solution synthesized by liquid-phase laser ablation.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Negative charge starts to build up and results in arc discharges which penetrate through and destruct the aluminum flakes (2) . Hydroxide and aluminum ions are then bonded to form Al(OH) 3 with hydrogen bubbles being liberated (3) . No sign of erosion‐corrosion was observed on the electrodes after reactions (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…[41] Hydroxide and aluminum ions are then bonded to form Al(OH) 3 with hydrogen bubbles being liberated (3). [42] No sign of erosion-corrosion was observed on the electrodes after reactions (data not shown). FE-SEM and EDS analysis result shows that submicron sized Al(OH) 3 crystallite with high purity is synthesized (Figure 2).…”
Section: Mp Mechanismmentioning
confidence: 91%